Expressions of ion co-transporter genes in salicylate-induced tinnitus and treatment effects of spirulina. Issue 1 (December 2016) - Hwang, Juen-Haur; Chan, Yin-Ching
Abstract Background Although the activity of tinnitus-related ion co-transporter are known, their mRNA expressions has seldom been reported. We aimed to investigate the mRNA expressions of tinnitus-related ion co-transporter genes, and treatment effects of Spirulina. Methods The mRNA expressions of K+ –Cl− co-transporter (KCC2) and Na-K-2Cl co-transporter 1 (NKCC1) genes in the cochlea and brain of mice were evaluated after tinnitus was induced by intraperitoneal injection of salicylate. The effects of spirulina water extract on these gene expressions were investigated. Results Compared to the control group, the tinnitus scores increased significantly, however, the salicylate-induced tinnitus could be reduced significantly by spirulina water extract. The tinnitus group had higher of borderline significance mRNA expression of KCC2 gene in the cochlear, significantly higher in the temporal lobes and in the frontal lobes. Meanwhile, compared to the tinnitus group, the spirulina group had significantly lower mRNA expression of KCC2 gene in the cochlear, temporal lobes, frontal lobes and parahippocampus/hippocampus. However, the NKCC1 mRNA expression was not significantly different between three groups in the cochlea and these brain areas. Conclusion Salicylate-induced tinnitus might be associated with increased mRNA expression of KCC2 gene, but not with mRNA expressions of NKCC1 gene in the cochlear and some tinnitus-related brain areas. Spirulina reduced the expression of KCC2 genes in salicylate-induced tinnitus.